Integrating Social Prescribing into Primary Care: Policy Implications and Educational Needs in Medan, Indonesia - Ni Made Nova Indriyani; Lisye Tiur Simanjuntak; Badrool Nizham; Ramakhrisnand Ramakhrisnand (Community Medicine and Education Journal, 2025)
Social prescribing (SP) is a growing approach to address the social determinants of health by linking patients in primary care with non-clinical community resources. Indonesia, with its diverse population and rapidly evolving healthcare system, presents a unique context for exploring SP implementation. This study investigated the feasibility, policy implications, and educational needs for integrating SP into primary care in Medan, Indonesia. A mixed-methods approach was employed. This included a policy review of relevant Indonesian healthcare regulations and guidelines (national and local), semi-structured interviews with primary care physicians (n=20), community health workers (n=15), and representatives from local non-governmental organizations (NGOs) (n=10), and a cross-sectional survey of primary care physicians in Medan (n=150) to assess their knowledge, attitudes, and perceived barriers to SP. Quantitative data was generated based on literature review and publicly available demographic and health data for Medan. Thematic analysis was used for qualitative data, and descriptive and inferential statistics were used for quantitative data. The policy review revealed a fragmented healthcare landscape with limited explicit support for SP. Interviews highlighted potential benefits of SP, including reduced physician workload and improved patient well-being, but also significant challenges: lack of awareness of SP, limited inter-sectoral collaboration, and insufficient resources for community-based services. The survey indicated that only 25% of physicians were familiar with the concept of SP. Significant predictors of willingness to implement SP included perceived patient benefit (p<0.001) and availability of referral pathways (p<0.01). Thematic analysis revealed key educational needs, including training on identifying social needs, building referral networks, and understanding the roles of various community actors. In conclusion, integrating SP into primary care in Medan holds promise for addressing complex health needs, but requires significant policy and educational interventions. Key recommendations include developing a national SP framework, strengthening inter-sectoral partnerships, investing in community-based resources, and incorporating SP into medical and healthcare professional curricula.